Cover Feature: Lithium Hydroxide Assisted Endo‐Selective [4+4]‐Photocycloaddition of Pyran‐2‐ones (Eur. J. Org. Chem. 16/2021). Issue 16 (20th April 2021) - Li, Lei; Turnbull, William L.; McDonald, Robert; West, F. G.
Abstract : The Cover Feature shows the light‐driven intramolecular [4+4]‐cycloaddition reaction of pyran‐2‐ones with 3‐acyl side‐chains terminated with furans. Irradiation at 0 °C in the presence of 1 equivalent of LiOHH2 O and sparteine cleanly converts these linked heterocycles into lactone‐bridged cyclooctenones with complete endo selectivity. A mechanistic rationale involving a templating effect by lithium cation can explain the observed stereoselectivity, which is the opposite to what is seen in other pyran‐2‐one [4+4]‐photocycloadditions. More information can be found in the Full Paper by F. G. West et al.